Therapeutic potential of coumarin bearing metal complexes: Where are we headed? - Balcioglu, Sevgi; Karatas, Mert Olgun; Ates, Burhan; Alici, Bulent; Ozdemir, Ismail (Pergamon-Elsevier Science Ltd, 2020)
The successfully application of some metallodrugs such as salvarsan, silver sulfadiazine and cisplatin in modern medicine launched the biological investigation of organometallic and metal-organic complexes. The availability and tunability of various ligands including N-heterocycles, phosphines, N-heterocyclic carbenes present an extended research area to chemists. In recent years, the preparation of the metal complexes of bioactive organic compounds is a new strategy. Coumarin derivatives are one of the classes of compounds used for this purpose, and many complexes of coumarin derivatives were prepared for enhanced biological activity, especially anticancer and antimicrobial. In this paper, we discuss the current situation of this topic.
Keywords: Coumarin derivatives; Metal complexes; Anticancer; Antimicrobial; Biological activity